Admittance and dielectric spectroscopy of polycrystalline semiconductors - Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
This text discusses about advantageous, powerful and limitations of admittance and dielectric spectroscopy in the characterization of polycrystalline semiconductors. In the context of polycrystalline semiconductors or dielectric materials, the admittance or dielectric frequency response analyses are shown to be sometimes more useful than impedance spectra analysis, mainly because information on the capacitances or deep trap states are possible to be monitored from admittance or dielectric spectra as a function of dopant concentration or annealing effects. The majority of examples of the application of admittance or dielectric analysis approach were here based on SnO2- and ZnO-based polycrystalline semiconductors devices presenting nonohmic properties. Examples of how to perform the characterization of Schottky barrier in such devices are clearly depicted. The approach is based on findings of the true Mott-Schottky pattern of the barrier by extracting the grain boundary capacitance value from complex capacitance diagram analysis. The equivalent circuit of such kind of devices is mainly consistent with the existence of three parallel elements: the high-frequency limit related to grain boundary capacitances, the complex incremental capacitance at intermediate frequency related to the deep trap relaxation and finally at low frequency region the manifestation of the conductance term representing the dc conductance of the multi-junction device. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: impedance spectroscopy; varistor